Upregulation of mNEIL3 in Ogg1-null cells is a potential backup mechanism for 8-oxoG repair. (13th October 2021) - Higgs, Ellen B; Godschalk, Roger; Langie, Sabine A S; van Schooten, Frederik-Jan; Hodges, Nikolas J
Abstract: Reactive oxygen species formation and resultant oxidative damage to DNA are ubiquitous events in cells, the homeostasis of which can be dysregulated in a range of pathological conditions. Base excision repair (BER) is the primary repair mechanism for oxidative genomic DNA damage. One prevalent oxidised base modification, 8-oxoguanine (8-oxoG), is recognised by 8-oxoguanine glycosylase-1 (OGG1) initiating removal and repair via BER. Surprisingly, Ogg1 null mouse embryonic fibroblasts (m Ogg1 −/− MEFs) do not accumulate 8-oxoG in the genome to the extent expected. This suggests that there are backup repair mechanisms capable of repairing 8-oxoG in the absence of OGG1. In the current study, we identified components of NER ( Ercc1, Ercc4, Ercc5 ), BER ( Lig1, Tdg, Nthl1, Mpg, Mgmt, NEIL3 ), MMR ( Mlh1, Msh2, Msh6 ) and DSB ( Brip1, Rad51d, Prkdc ) pathways that are transcriptionally elevated in m Ogg1 −/− MEFs. Interestingly, all three nucleotide excision repair genes identified: Ercc1 (2.5 ± 0.2-fold), Ercc4 (1.5 ± 0.1-fold) and Ercc5 (1.7 ± 0.2-fold) have incision activity. There was also a significant functional increase in NER activity (42.0 ± 7.9%) compared to WT MEFs. We also observed upregulation of both Neil3 mRNA (37.9 ± 1.6-fold) and protein in m Ogg1 −/− MEFs. This was associated with a 3.4 ± 0.4-fold increase in NEIL3 substrate sites in genomic DNA of cells treated with BSO, consistent with the ability of NEIL3 to remove 8-oxoG oxidation products from genomic DNA. In conclusion, we suggest that in Ogg1 -null cells, upregulation of multiple DNA repair proteins including incision components of the NER pathway and Neil3 are important compensatory responses to prevent the accumulation of genomic 8-oxoG.